2014
DOI: 10.5137/1019-5149.jtn.11847-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Intrasellar clear cell meningioma mimicking invasive pituitary adenoma: a case report and review of literature

Abstract: The authors report on a 55-year-old man with complaints of intermittent pulsatile headache for 6 months, vision loss of the right eye and diplopia for 2 months. A magnetic resonance image (MRI) showed a large heterogeneously enhanced intrasellar mass lesion, occupying the entire hypophyseal fossa and extending into the sphenoid sinus. The patient underwent microscopic transsphenoidal surgery for removal of the tumor. Microscopic examination with hematoxylin&eosin and immunohistochemical staining of the tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Few reports have described the diagnosis of a parasellar clear cell meningioma, all of which occurred as a single tumor. 33 42 43 44 45 46 Although more common in young adults and children, sellar region clear cell meningioma was diagnosed in 11- to 79-year-old patients. 33 42 43 44 45 46 Additionally, in all but one case, a dural attachment was seen, 42 43 44 45 46 while a single case described the occurrence of an intrasellar clear cell meningioma without a dural attachment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few reports have described the diagnosis of a parasellar clear cell meningioma, all of which occurred as a single tumor. 33 42 43 44 45 46 Although more common in young adults and children, sellar region clear cell meningioma was diagnosed in 11- to 79-year-old patients. 33 42 43 44 45 46 Additionally, in all but one case, a dural attachment was seen, 42 43 44 45 46 while a single case described the occurrence of an intrasellar clear cell meningioma without a dural attachment.…”
Section: Discussionmentioning
confidence: 99%
“… 33 42 43 44 45 46 Although more common in young adults and children, sellar region clear cell meningioma was diagnosed in 11- to 79-year-old patients. 33 42 43 44 45 46 Additionally, in all but one case, a dural attachment was seen, 42 43 44 45 46 while a single case described the occurrence of an intrasellar clear cell meningioma without a dural attachment. 33 Therefore, given the rarity of clear cell meningioma arising as a single-region tumor, this further emphasizes the diagnostic conundrum seen in our case where a gonadotropic adenoma was simultaneously diagnosed with a suprasellar clear cell meningioma without the classic dural attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 21 ] Meanwhile, giant intrasellar meningiomas mimicking pituitary adenomas have been well described in previous studies. [ 22 , 23 ] However, few articles regarding collision tumors composed of pituitary adenoma and meningioma have been published. To date, Karsy et al [ 9 ] reported the only case study of coincident pituitary adenoma and sellar meningioma in which mental changes were the chief complaint and a non-secreting pituitary adenoma was identified by pituitary laboratory tests and postoperative pathology.…”
Section: Discussionmentioning
confidence: 99%